2017
DOI: 10.22159/ajpcr.2017.v10i11.18864
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Combined With Standard Antiemetic Regimens for Prevention of Chemotherapy Therapy-Induced Nausea and Vomiting: A Single-Center Experience From South India

Abstract: Objectives: Olanzapine, an antipsychotic agent, exhibits significant antiemetic properties due to its inhibitory activity on neurotransmitters at multiple receptors involved in chemotherapy-induced nausea and vomiting (CINV). CINV can have an immensely negative impact on patient's quality of life (QOL) and daily activities. Our objectives were to determine the effectiveness of adding olanzapine to standard antiemetic regimens for the prevention of CINV in cancer patients and to compare the QOL of such patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Improvement of emotional functioning was reported among patients of olanzapine groups in all three studies that used the EORTC QLQ‐C30 as a HRQoL measure instrument ( P < 0.05) . In two of these three studies, the change of cognitive functioning in olanzapine groups was observed, but there was no statistical significance ( P > 0.05) . In one study, which adopted the WHOQOL‐BREF, mental health of patients was not improved significantly at the end of olanzapine treatment ( P > 0.05)…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Improvement of emotional functioning was reported among patients of olanzapine groups in all three studies that used the EORTC QLQ‐C30 as a HRQoL measure instrument ( P < 0.05) . In two of these three studies, the change of cognitive functioning in olanzapine groups was observed, but there was no statistical significance ( P > 0.05) . In one study, which adopted the WHOQOL‐BREF, mental health of patients was not improved significantly at the end of olanzapine treatment ( P > 0.05)…”
Section: Resultsmentioning
confidence: 97%
“…Five of six studies reported results of general HRQoL change. In two of three studies which used the EORTC QLQ‐C30, HRQoL was significantly improved among patients who received olanzapine both in short term (6 days, P < 0.01) and in long term (after four cycles of chemotherapy, P = 0.01) compared with the non‐olanzapine group. The remaining one indicated that the general HRQoL status of patients in the olanzapine group was stable between the 8 th and 10 th day after chemotherapy, whereas it was worse in the control group .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations